HbA1c level is associated with the development of heart failure with recovered ejection fraction in hospitalized heart failure patients with type 2 diabetes. (15th January 2023) - Yang, Chen Die; Aihemaiti, Muladili; Quan, Jin Wei; Chen, Jia Wei; Shu, Xin Yi; Ding, Feng Hua; Shen, Wei Feng; Lu, Lin; Zhang, Rui Yan; Pan, Wen Qi; Wang, Xiao Qun
Abstract: Background: Due to advances in medical treatments, a substantial proportion of heart failure (HF) patients with reduced left ventricular ejection fraction (EF, HFrEF) have experienced partial or complete recovery of EF, termed HFrecEF, and markedly improved clinical outcomes. In the present study, we sought to investigate the relationship between glycemic control and the incidence of HFrecEF in hospitalized HFrEF patients with type 2 diabetes mellitus (T2DM). Methods: A total of 463 hospitalized T2DM patients with HFrEF were consecutively enrolled. Follow-up echocardiogram was performed after around 12 months. Patients who had an absolute EF improvement ≥10% and a second EF > 40% were classified into HFrecEF, and those who did not meet these criteria were defined as persistent HFrEF. Results: During the 12-month follow-up, 44.5% of T2DM patients developed HFrecEF. Patients with HFrecEF had significantly lower HbA1c level than those with persistent HFrEF (6.5% [IQR 5.8% ∼ 7.2%] vs. 6.7% [IQR 6.1% ∼ 7.8%], P  = 0.003), especially in HF of an ischemic etiology. HbA1c levels were inversely correlated with changes in EF during follow-up. After multivariate adjustment, every 1% increase in HbA1c conferred a 17.4% (OR: 0.826 [95% CI 0.701–0.968]) lower likelihood of HFrecEF. Compared to patients with good glycemic control (HbA1c ≤ 6.2%), those with poor glycemic control (HbA1c > 7.1%) had a 52.0% (OR: 0.480 [95% CI 0.281–0.811] decreased likelihood of HFrecEF. Conclusions: This study demonstrates that uncontrolled HbA1c level is associated with compromised development of HFrecEF in T2DM patients with HF, especially in those with an ischemic etiology. Highlights: Higher HbA1c level is independently associated with compromised development of HFrecEF in patients with type 2 diabetes. Ischemic heart failure is more prone to be affected by hyperglycemia during myocardial functional recovery. Assessing HbA1c levels aids in prediction of myocardial functional recovery in heart failure patients with type 2 diabetes.